Some vital aspects of using the arrest as a punishment in accordance with the legislation of the Republic of Kazakhstan - Aldiyarkhan М.А. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2022)
The article investigates results and other relevant legal issues of the use of punishment in the form of arrest by convicts in the criminal legislation of the Republic of Kazakhstan. The current Criminal Code, adopted on July 3, 2014, states that criminal offenses, depending on the degree of public danger and punishability, are divided into crimes and criminal offenses. I conducted a study on the type of criminal punishment in the form of «arrest» used for committing a criminal offense. An explanation is also given on the concept of a crime and a criminal offense in the Criminal Code of the Republic of Kazakhstan. The article represents comparative research of the brief history and practice of applying punishment under arrest in the legislation of the Republic of Belarus and the Russian Federation, as well as in the criminal legislation of the Republic of Kazakhstan. The author makes his scientific conclusions for improving the national mechanism for applying arrest as a punishment conducting a legal analysis of national legislation and the legislation of some foreign states.